Lead Contamination in Pangasius Djambal in the Dam of Kalitidu District, Bojonegoro District: An Environmental Health Risk Study - Husniyah, Ami; Nurika, Globila; Ellyke, Ellyke (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: One of the areas passed by the Bengawan Solo River is Bojonegoro. Many Bojonegoro people find fish at the point of Bendung Gerak, Ngringinrejo Village. One of the fish that is often caught is Pangasius djambal. At this location, the dominant waste contamination comes from agricultural and domestic waste. Lead can contaminate water and enter through the food chain in fish which are later eaten by humans. The purpose of this study was to analyze the environmental health risk of lead (Pb) content in Pangasius djambal in Bendung Gerak Ngringinrejo Village, Kalitidu District, Bojonegoro Regency. Methods: This research used field environmental health risk analysis method. The total sampling of the community was 50 respondents and was taken using accidental sampling. Community sample criteria are those who consume Pangasius djambal within 1 year. Environmental samples are Pangasius djambal taken at 3 points and analyzed using the Atomic Absorption Spectrophotometry (AAS) method. Results and Discussion: The results showed lead intakes at points A, B, and C were 0.0018 mg/kg/day, 0.0639 mg/kg/day, and 0.0012 mg/kg.day, respectively. The results show the RQ value of point B RQ>1 (unsafe), while points A and C are RQ≤1 (safe). It can be caused by several factors such as body weight, intake rate, consumption frequency, exposure duration, and lead concentration. Conclusion: Based on these results, it is necessary to do risk management at point B.